Is Response to Genotoxic Stress Similar in Populations of African and European Ancestry? A Study of Dose-Response After in vitro Irradiation - Soumboundou, Mamadou; Dossou, Julien; Kalaga, Yossef; Nkengurutse, Innocent; Faye, Ibrahima; Guingani, Albert; Gadji, Macoura; Yameogo, Koudbi J.; Zongo, Henri; Mbaye, Gora; Dem, Ahmadou; Diarra, Mounibé; et al. (Frontiers in Genetics, 2021)
Background: Exposure to genotoxic stress such as radiation is an important public health issue affecting a large population. The necessity of analyzing cytogenetic effects of such exposures is related to the need to estimate the associated risk. Cytogenetic biological dosimetry is based on the relationship between the absorbed dose and the frequency of scored chromosome aberrations. The influence of confounding factors on radiation response is a topical issue. The role of ethnicity is unclear. Here, in a cohort of populations, we compared the dose-response curves obtained after irradiation of circulating lymphocytes from healthy donors of African and European ancestry. Material and methods: Blood samples from six Africans living in Africa, from five Africans living in Europe, and from five Caucasians living in Europe were exposed to various doses (0–4 Gy) of X-rays at a dose-rate of 0.1Gy/min using an X-RAD320 irradiator. A validated cohort composed of 14 healthy African living in three African countries was included, and blood samples were irradiated using the same protocols. Blood lymphocytes were cultured for 48 h and chromosomal aberrations scored by telomere and centromere staining. The distribution of dicentric chromosomes was determined, and the Kruskal-Wallis test was used to compare the dose-response curves of the two populations. Results: No spontaneous dicentric chromosomes were detected in African donors, thus establishing a very low background of unstable chromosomal aberrations relative to the European population. There was a significant difference in the dose response curves between native African and European donors. At 4 Gy, African donors showed a significantly lower frequency of dicentric chromosomes (p = p=8.65 10-17), centric rings (p=4.0310-14), and resulting double-strand-breaks (DSB) (p=1.32 10-18) than European donors. A significant difference was found between African donors living in Europe and Africans living in Africa. Conclusion: This is the first study to demonstrate the important role of ethnic and environmental factors that may epigenetically influence the response to irradiation. It will be necessary to establish country of origin specific dose response curves to practice precise and adequate biological dosimetry. This work opens new perspective for the comparison of treatments based on genotoxic agents, such as irradiation.